Climate change, interrupted : representation and the remaking of time - Leckie, Barbara (Stanford University Press, 2022)
"In this moment of climate precarity, Victorian studies scholar Barbara Leckie considers the climate crisis as a problem of time. Spanning the long nineteenth century through our current moment, her interdisciplinary treatment of climate change at once remakes time and illustrates that the time for climate action is now. Climate Change, Interrupted argues that linear, progress-inflected temporalities are not adequate to a crisis that defies their terms. Instead, this book advances a theory and practice of interruption to rethink prevailing temporal frameworks. At the same time, it models the anachronistic, time-blending, and time-layering temporality it advances. In a series of experimental chapters informed by the unlikely trio of Walter Benjamin, Donna Haraway, and Virginia Woolf, Leckie reinflects and cowrites the traditions and knowledges of the long nineteenth century and the current period in the spirit of climate action collaboration. The current moment demands as many approaches as possible, invites us to take risks, and asks scholars and activists adept at storytelling to participate in the conversation. Climate Change, Interrupted, accordingly, invests in interruption to tell a different story of the climate crisis"--